Living with the Sea: Everyday Rhythms, Social Space, and Cultural Meaning in Sangihe Island Communities - Muhammad Riyadi; Eka Aprilya Handayani; Hildayani Hildayani (Professorline, 2026)
Island communities in the Sangihe archipelago organize their social life through everyday practices that are inseparable from the surrounding maritime environment. This article examines how daily rhythms, shared social spaces, and cultural meanings shape collective life in Sangihe from a sociological perspective. Rather than focusing on economic productivity or formal governance, the article emphasizes lived experience as the foundation of social organization. By approaching island society through ordinary practices, the article highlights how social cohesion is produced through repetition, proximity, and shared understanding. Time, space, and routine interaction are treated not as background conditions but as active elements in shaping social relations. This perspective contributes to broader discussions on society and culture by demonstrating how island communities sustain continuity and adapt to change through everyday life. It positions Sangihe as an example of how social order in Global South Island contexts is grounded in lived maritime experience.